THE DUTCH CARTOGRAPHY’S GOUDEN EEUW, BETWEEN ART AND INDUSTRY. - Michele Castelnovi (Bollettino della Società Geografica Italiana, 2019)
A recent article by Alessandro Ricci shows the relationship between the visual arts (such as painting) and the large cartographic production in the Dutch Golden Age (1588-1702). But we must not ignore the link between cartography and industrial production: both the characteristics of printig, and for the dissemination of geographical knowledge in many copies, primarly through the East India Company (VOC). Protestant culture was particularly suited to accommodate the press, while the Catholic culture continued to appreciate the manuscript maps, drawn by hand. However, one of the most interesting case study is the great Novus Atlas Sinensis by Martino Martini, an Italian Jesuit who, after 17 years of missionary work in China, in 1655 chose to print his own information in the typography of a Protestant, Johan Blaeu: official cartographer of the VOC in Amsterdam.